Por um ensino de várias cores: formação de professores à luz da história cultura afro-brasileira e africana - Marchi, Sandra Aparecida (2016)
The Federal Law No. 10,639, enacted in 2003 providing for the inclusion in school curricula the study of history and Afro-Brazilian and African, emerges as a tool and opportunity to promote affirmative action within the school context and consequently resulting in changes in society . However, the introduction of a law by itself is not enough, you must provide the teaching conditions of applicability. And that's what this paper seeks to: provoke discussion in order to analyze, reflect, discuss and implement the ongoing training of Early Childhood Education teachers (as affirmative action policies must be developed from an early age), and final series (specifically curricular component History) in the municipality of Giruá, the education of ethnicracial relations. Law 10.639 / 03, which establishes the obligation of the Teaching of Afro-Brazilian culture and African in Basic Education and the National Curriculum Guidelines for the Education of Ethnic Relations Race, sought to draw national curriculum guidelines for the different levels of education Brazilian. The training referred to in law should equip teachers so that they will develop in the class room content, methodologies and practices that address the history and black culture, spreading basic knowledge of what is to contemplate the African culture and african- Brazilian. Whereas teachers learn to teach in different ways, this project proposes to contribute to teacher training, with the central theme of the education of ethnic-racial relations. The work will develop in the form of short courses, which are arranged in four different moments with specific approaches each. The work aims to create opportunities for teaching discussions on this demand now that it must be in the form of law. The methodological framework is based on bibliographic studies and document analysis. The investment in the continuing education of teachers' education levels served by the education municipal system is of paramount importance, aiming thereby create opportuniti.